Optimization of the Biodiesel Production via Heterogenous Catalyzed Transesterification of Neem Seed Oil using Response Surface Methodology (RSM) - Adamu Zubairu Utono; Fakai, Rufai Usman; Babanladi, Muhammad Inusa (International Journal of Applied Research and Sustainable Sciences, 2023)
Biodiesel production from neem seed oil and performance evaluation of three selected catalyst was investigated. Neem seed oil was used for its suitability as feedstock for biodiesel production. The oil was extracted using soxhlet extraction method using n- hexane as a solvent and yielded 42.1%. Biodiesel was produced according to box behnken design in response surface methodology, to study the effect of experimental variables such as methanol to oil ratio, catalyst concentration, temperature and reaction time. Three (3) catalysts were used during the process namely CaO, MgO and ZnO. The model shows the highest of biodiesel yield of 89% w/w using MgO at 9:1 methanol to oil ratio, catalyst concentration of 1.1% w/w, reaction time was 120 minutes, and temperature was kept constant at 600C. ZnO performance on the transesterification of neem seed oil to biodiesel yielded 88% w/w at 6:1methanol to oil ratio, 0.8% w/w catalyst concentration and 90 minutes was the reaction time. Similarly CaO performance on the trasesterification of neem seed oil to biodiesel yielded percentage of 84 % at 6:1, catalyst concentration of 0.8% w/w and reaction time was 90 minutes. Methanol to oil ratio and catalyst concentration has significant effect on trasensterification of neem seed oil to biodesel than reaction time among others studied. The physiochemical properties of produced biodiesel was analyzed and characterized for its Fatty Acid Methyl Ester (FAME) profile using GCMS. Fuel properties of the biodiesel obtained are within the recommended standard of ASTM and suitable to be an alternative source of fuel.